Radial variation of sulfur and oxygen ions in the Io plasma torus as deduced from remote observations by Hisaki. Issue 3 (7th March 2017) - Yoshioka, K.; Tsuchiya, F.; Kimura, T.; Kagitani, M.; Murakami, G.; Yamazaki, A.; Kuwabara, M.; Suzuki, F.; Hikida, R.; Yoshikawa, I.; Bagenal, F.; Fujimoto, M.
Abstract: The Io plasma torus, situated in the Jovian inner magnetosphere (6–8 Jovian radii from the planet) is filled with heavy ions and electrons, a large part of which are derived from Io's volcanos. The torus is the key area connecting the primary source of plasma (Io) with the midmagnetosphere (>10 Jovian radii), where highly dynamic phenomena are taking place. Revealing the plasma behavior of the torus is a key factor in elucidating Jovian magnetospheric dynamics. A global picture of the Io plasma torus can be obtained via spectral diagnosis of remotely sensed ion emissions generated via electron impact excitation. Hisaki, an Earth‐orbiting spacecraft equipped with an extreme ultraviolet spectrograph Extreme Ultraviolet Spectroscope for Exospheric Dynamics, has observed the torus at moderate spectral resolution. The data have been submitted to spectral analysis and physical chemistry modeling under the assumption of axial symmetry. Results from the investigation are radial profiles of several important parameters including electron density and temperature as well as ion abundances. The inward transport timescale of midmagnetospheric plasma is obtained to be 2–40 h from the derived radial profile for the abundance of suprathermal electrons. The physical chemistry modeling results in a timescale for the outward transport of Io‐derived plasma of around 30 days. The ratio between inward and outward plasma speed (~1%) is consistent with the occurrence rate of depleted flux tubes determined using in situ observations by instruments on the Galileo spacecraft. Key Points: Hisaki enables EUV spectral diagnosis of the Io torus for both S and O ions by eliminating the geocoronal contamination Radial profiles are derived for the density of electrons and various ion species, plus electron temperature Timescales of inward and outward plasma transport are estimated to be 2–40 h and 30 days, respectively